Planning for conflict transformation after U.S. military intervention - Smith, Candy S. (My University, 2025)
This dissertation investigates how U.S. Department of Defense (DoD) planning for post-conflict stability operations affects conflict transformation following military interventions. The persistent challenges associated with post-conflict stabilization efforts following U.S. military interventions in fragile and/or failed states underscore a critical gap in understanding how military planning influences conflict transformation. Conventional academic discourse largely attributes the failures of U.S. military stabilization to inadequate problem comprehension or the deterioration of civil-military relations. This dissertation posits an alternative perspective: the root cause of these shortcomings lies in an uninformed understanding of the intricate process by which planning genuinely transforms conflict into durable peace, one that cultivates a stable and strengthened representative government. Using conflict transformation literature, the research uses expectations derived from literature to focus on three core components – understanding the conflict, establishing an inclusive and synchronized planning framework, and creating and sustaining national mechanisms of governance. The study employs fuzzy-set Qualitative Comparative Analysis (fsQCA) to assess whether the presence of these planning conditions leads to successful conflict transformation, defined as the emergence of a stable and strengthened representative government. Using fsQCA to systematically examine eight instances of U.S. military intervention from 1989 to 2003, the analysis tests four hypotheses linking planning elements to post-conflict outcomes. The dissertation also provides detailed case studies of U.S. interventions in Afghanistan (2001), Haiti (1995), and Iraq (2003) to explain the analysis specific to historical case studies. The findings suggest that understanding the conflict is a necessary condition for conflict transformation and that two distinct pathways: one where understanding conflict is combined with efforts to build national mechanisms and another where understanding is combined with the absence of a fully integrated framework are sufficient for the outcome. By bridging planning doctrine with conflict transformation theory, this dissertation provides a novel theoretical framework and methodological approach for evaluating and improving U.S. military planning for stability operations. The research contributes to both academic scholarship and policy development, emphasizing the need for comprehensive, adaptive planning strategies to guide future U.S. military interventions and post-conflict engagements.
Keywords: Conflict transformation; Military planning; QCA; Stability operations